Research on the Vulnerability of Government Procurement of Elderly Care Services: A Complex Network Perspective - Yuting Zhang; Lan Xu; Zhengnan Lu (Complexity)
The policy of government procurement of elderly care services has the vulnerability characteristics that all complex systems have. To maintain the policy’s robustness, this paper studies the vulnerability of government procurement of elderly care services from the perspective of complex network. Case analysis and sample statistics are used to obtain the vulnerability influencing factors of the policy. Then, complex network diagram of vulnerability influencing factors is constructed through Pajek software. The compatibility coefficient is used to investigate the network’s overall vulnerability from a macro perspective. From a micro perspective, a vulnerability index of the complex network is applied to measure each node’s vulnerability value, and the vulnerability priority of the nodes is established. Results show that government purchasing power and supervisory bodies’ diversity are at the first priority. The remaining vulnerability influencing factors are at the second and the third priority.